INTEGRATION OF BIOLOGICAL AND CHEMICAL ADVANCES NATURAL SCIENCES IN MEDICAL EDUCATION: NEW APPROACHES AND technologies (Uzbekistan Open Conference, 2025)
The article addresses the pressing issue of strengthening the role of biological and chemical sciences in medical education. It analyzes theoretical foundations and practical models for integrating the achievements of these natural sciences into the training of future physicians. Particular attention is paid to modern teaching methods - problem-based learning, case-based learning, and the use of laboratory and digital technologies. The paper concludes with recommendations for transforming traditional medical education and outlines strategies for enhancing the integration of biology and chemistry into the curriculum.